ESTUDO DA ADIÇÃO DE CULTURA PROBIÓTICA ANTERIOR E POSTERIOR À FERMENTAÇÃO DE BEBIDAS LÁCTEAS. - Poll, Raysa; Fiorentini, Angela M.; Klajn, Vera M.; Rosso, Ana C.; Ballus, Cristiano A.; Balbom, Everton B.; Meira, Stela M. M. (Salão do Conhecimento, 2013)
Resumo